The Socialization of Biofortification to Overcome Stunting in Kuala Dua Village: Sosialisasi Biofortifikasi Untuk Mengatasi Stunting Di Desa Kuala Dua - Hery Medianto Kurniawan; Ellyta Ellyta; Donna Youlla (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Biofortification technology is an intervention activity that has an effort to increase the concentration of micronutrients in food. The adoption of farmers is very good, indicated by the increasing biofortified farming activities in Kuala Dua Village. Thisincrease can be seen from the achievement of the cropping index from 200 to 300 and production from 4 tonnes per hectare to an average of between 6 -tonnes per hectare. It also can be concluded that the farmer’s adoption is very good, indicated by the increasing biofortified farming activities in Kuala Dua Village. It can be seen from the achievement of a cropping index from 200 to 300 and production from 4 tonnes per hectare to between 6 -7 tonnes per hectare. The results of this can be used for the prevention of stunting in Kuala Dua Village, Sungai Raya District, Kubu Raya Regency